2008
DOI: 10.1089/end.2007.0315
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Orchiopexy for Treating Inguinal Canalicular Palpable Undescended Testis

Abstract: The laparoscopic approach to orchiopexy is a safe way to descend the inguinal canalicular palpable testis. It offers several advantages of a minimally invasive technique and yield effective results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Other researchers also report this experience with similar results in the management of the inguinal hernia during orchidopexy. 3,4 High recurrence rates of up to 26% have been described in the recent literature with using the Awl technique, or SEAL technique (subcutaneous endoscopically assisted ligation), in which a curved or straight stainless steel needle is introduced percutaneously anterolateral to the internal ring, passing a circumferential ligature, without resection of the processus vaginalis. 5,6 Some other series report very low recurrence rates of 0.73%-4.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also report this experience with similar results in the management of the inguinal hernia during orchidopexy. 3,4 High recurrence rates of up to 26% have been described in the recent literature with using the Awl technique, or SEAL technique (subcutaneous endoscopically assisted ligation), in which a curved or straight stainless steel needle is introduced percutaneously anterolateral to the internal ring, passing a circumferential ligature, without resection of the processus vaginalis. 5,6 Some other series report very low recurrence rates of 0.73%-4.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from He and coworkers 18 reported 103 inguinal canalicular palpable UDT that were managed with laparoscopy. From 90 patients, only one complication was encountered and occurred at the beginning of the surgeon's learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Our procedure involved only cutting off a portion of the PV wall, in which cremaster muscle fibers are included, along the spermatic pedicle, instead of the separation of the vas and vessels from the PV and ligation of the PV high at its neck, because the open IIR is closed from inside of the abdomen by the Endoneedle technique (Endo, et al, 2009). For delivery of the testis, a neo-ring lateral to the bladder and medial to the median umbilical ligament has been widely utilized by employing an additional scrotal trocar for intra-abdominal and high canalicular testes (Poppas, et al, 1996, He, et al, 2008. The presence of PPV is ignored in the description of operation procedures in most reports (Samadi, et al, 2003, Chang, et al, 2001, Kim, et al, 2010, Moursy, et al, 2010, and recent consensus in the literature has been to leave the ring open because of rare occurrence of postoperative inguinal hernia (Riquelme, et al, 2006, Mohta, et al, 2003, although Poppas et al included closure of the defect using a stapling device if a hernia was present (Poppas, et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Ziylan O, et al reported that patients requiring reorchiopexy had inadequate repair of inguinal hernia or PPV in 62.5% of cases, which was considered to be an important factor leading to failure after surgical treatment of undescended testis (Ziylan, et al, 2004). Essentially, cryptorchidism is frequently associated with PPV as He D., et al reported associated PPV in 90.3% of ipsilateral side and 15.6% of contralateral side (He, et al, 2008). In our series, 29.6% of patients had associated hernia/hydrocele, and 84.1% of patients had ipsilateral PPV and 35.1% had cPPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation